BCI-FES With Multimodal Feedback for Motor Recovery Poststroke - Remsik, Alexander B.; van Kan, Peter L. E.; Gloe, Shawna; Gjini, Klevest; Williams, Leroy; Nair, Veena; Caldera, Kristin; Williams, Justin C.; Prabhakaran, Vivek (Frontiers in Human Neuroscience, 2022)
An increasing number of research teams are investigating the efficacy of brain-computer interface (BCI)-mediated interventions for promoting motor recovery following stroke. A growing body of evidence suggests that of the various BCI designs, most effective are those that deliver functional electrical stimulation (FES) of upper extremity muscles contingent on movement intent. More specifically, BCI-FES interventions utilize algorithms that isolate motor signals -- user-generated intent-to-move neural activity recorded from cerebral cortical motor areas -- to drive electrical stimulation of individual muscles or muscle synergies. BCI-FES interventions aim to recover sensorimotor function of an impaired extremity by facilitating and/or inducing long-term motor learning-related neuroplastic changes in appropriate control circuitry. We developed a noninvasive, electroencephalogram based BCI-FES system that delivers closed-loop neural activity-triggered electrical stimulation of targeted distal muscles while providing the user with multimodal sensory feedback. This BCI-FES system consists of three components: 1) EEG acquisition and signal processing to extract real-time volitional and task-dependent neural command signals from cerebral cortical motor areas, 2) FES of muscles of the impaired hand contingent on the motor cortical neural command signals, and 3) multimodal sensory feedback associated with performance of the behavioral task, including visual information, linked activation of somatosensory afferents through intact sensorimotor circuits, and electro-tactile stimulation of the tongue. In this report, we describe device parameters and intervention protocols of our BCI-FES system which, combined with standard physical rehabilitation approaches, has proven efficacious in treating upper extremity motor impairment in stroke survivors, regardless of level of impairment and chronicity.